The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Volume 3B: Heat Transfer 2013
DOI: 10.1115/gt2013-94716
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Predictions From Conjugate Heat Transfer Analysis of a Film-Cooled Turbine Vane to Experimental Data

Abstract: Conjugate heat transfer analysis was conducted on a 648 hole film cooled turbine vane using Code Leo and compared to experimental results obtained at the Air Force Research Laboratory Turbine Research Facility. An unstructured mesh with fully resolved film holes for both fluid and solid domains was used to conduct the conjugate heat transfer simulation on a desktop PC with eight cores. Initial heat flux and surface metal temperature predictions showed reasonable agreement with heat flux measurements but under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The use of radiation based wall temperature measurents in hot test rigs can result in poor agreement with CHT CFD, possibly due to emissivity calibration problems, as the emissivity is a function of temperature [30,31]. When imbedded thermocouples are used as in the present work, there is a growing body of evidence, particularly for metal turbine blade studies of agreement between CHT CFD predictions and metal temperature measurements [32,33]. For flat wall effusion cooling Oguntade et al [34 -36], have shown good agreement with experimental hot test result for Nimonic-75 effusion walls with imbedded thermocouples.…”
Section: Previous Work On Cht Cfd In Gas Turbinesmentioning
confidence: 91%
“…The use of radiation based wall temperature measurents in hot test rigs can result in poor agreement with CHT CFD, possibly due to emissivity calibration problems, as the emissivity is a function of temperature [30,31]. When imbedded thermocouples are used as in the present work, there is a growing body of evidence, particularly for metal turbine blade studies of agreement between CHT CFD predictions and metal temperature measurements [32,33]. For flat wall effusion cooling Oguntade et al [34 -36], have shown good agreement with experimental hot test result for Nimonic-75 effusion walls with imbedded thermocouples.…”
Section: Previous Work On Cht Cfd In Gas Turbinesmentioning
confidence: 91%
“…The insufficient diffusion led to overpredicted cooling effectiveness for attached jets and underpredicted effectiveness for detached jets. Ni et al [20,21] simulated a fully film cooled vane and endwall geometry under flow conditions consistent with a dual spool engine with a pressure ratio of 40. The conjugate simulations were performed using the standard k-x turbulence model.…”
Section: Relevant Literaturementioning
confidence: 99%
“…Actually, CHT analysis is in the interest of gas turbine manufacturers to optimize cooling schemes and improve turbine durability during design and before committing to hardware. 36…”
Section: Discussionmentioning
confidence: 99%